Characteristics in Non-Vitamin K Antagonist Oral Anticoagulant-Related Intracerebral Hemorrhage - Gerner, Stefan Toni; Ringleb, Peter A.; Purrucker, Jan; Rizos, Timolaos (Stroke, 2019)
Background and Purpose—Given inconclusive studies, it is debated whether clinical and imaging characteristics, as well as functional outcome, differ among patients with intracerebral hemorrhage (ICH) related to vitamin K antagonists (VKA) versus non-vitamin K antagonist (NOAC)-related ICH. Notably, clinical characteristics according to different NOAC agents and dosages are not established.Methods—Multicenter observational cohort study integrating individual patient data of 1328 patients with oral anticoagulation-associated ICH, including 190 NOAC-related ICH patients, recruited from 2011 to 2015 at 19 tertiary centers across Germany. Imaging, clinical characteristics, and 3-months modified Rankin Scale (mRS) outcomes were compared in NOAC- versus VKA-related ICH patients. Propensity score matching was conducted to adjust for clinically relevant differences in baseline parameters. Subgroup analyses were performed regarding NOAC agent, dosing and present clinically relevant anticoagulatory activity (last intake <12h/24h or NOAC level >30 ng/mL).Results—Despite older age in NOAC patients, there were no relevant differences in clinical and hematoma characteristics between NOAC- and VKA-related ICH regarding baseline hematoma volume (median [interquartile range]: NOAC, 14.7 [5.1-42.3] mL versus VKA, 16.4 [5.8-40.6] mL; P=0.33), rate of hematoma expansion (NOAC, 49/146 [33.6%] versus VKA, 235/688 [34.2%]; P=0.89), and the proportion of patients with unfavorable outcome at 3 months (mRS, 4-6: NOAC 126/179 [70.4%] versus VKA 473/682 [69.4%]; P=0.79). Subgroup analyses revealed that NOAC patients with clinically relevant anticoagulatory effect had higher rates of intraventricular hemorrhage (n/N [%]: present 52/109 [47.7%] versus absent 9/35 [25.7%]; P=0.022) and hematoma expansion (present 35/90 [38.9%] versus absent 5/30 [16.7%]; P=0.040), whereas type of NOAC agent or different NOAC-dosing regimens did not result in relevant differences in imaging characteristics or outcome.Conclusions—If effectively anticoagulated, there are no differences in hematoma characteristics and functional outcome among patients with NOAC- or VKA-related ICH.Clinical Trial Registration